2002
DOI: 10.1074/jbc.m200427200
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived Growth Factor (PDGF)-induced Tyrosine Phosphorylation of the Low Density Lipoprotein Receptor-related Protein (LRP)

Abstract: The low density lipoprotein receptor-related protein (LRP) 1 is a large endocytic receptor containing a 515-kDa heavy chain to which ligands bind and a non-covalently associated 85-kDa light chain containing a transmembrane and cytoplasmic domain (for review see Ref. 1). LRP is one of 12 or more receptors that make up the LDL receptor superfamily and is essential for embryonic development in mice (2). A remarkable feature of LRP is its ability to bind and mediate the internalization of a diverse array of ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
240
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 235 publications
(253 citation statements)
references
References 52 publications
11
240
2
Order By: Relevance
“…We then investigated pro-cath-D internalization by LRP1 using MEF that lacked M6P receptors ( Figure 1B Pro-cath-D and ectopic cath-D do not modulate LRP1b-chain tyrosine phosphorylation in fibroblasts The LRP1 at the plasma membrane is located in clathrin-coated pits and lipid rafts (Boucher et al, 2002;Zhang et al, 2004;Wu and Gonias, 2005), and it has been suggested that there are LRP1-induced signal transduction pathways triggered by tyrosine phosphorylation or RIP in lipid rafts (Boucher et al, 2002; von Cathepsin D, endocytosis and LRP1 RIP D Derocq et al Arnim et al, 2005;Wu and Gonias, 2005). We observed that LRP1b overproduction directs pro-cath-D to the lipid rafts (Beaujouin et al, 2010), suggesting that cath-D modulates the tyrosine phosphorylation of LRP1, as shown for the PDGF-BB (Boucher et al, 2002;Loukinova et al, 2002;Boucher and Gotthardt, 2004;Newton et al, 2005) and CTGF (Yang et al, 2004) growth factors, the tPA serine protease (Hu et al, 2006) and in fibroblasts transformed with v-Src (Barnes et al, 2001(Barnes et al, , 2003. We next investigated the effect of pro-cath-D on the tyrosine phosphorylation of LRP1b in fibroblasts.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…We then investigated pro-cath-D internalization by LRP1 using MEF that lacked M6P receptors ( Figure 1B Pro-cath-D and ectopic cath-D do not modulate LRP1b-chain tyrosine phosphorylation in fibroblasts The LRP1 at the plasma membrane is located in clathrin-coated pits and lipid rafts (Boucher et al, 2002;Zhang et al, 2004;Wu and Gonias, 2005), and it has been suggested that there are LRP1-induced signal transduction pathways triggered by tyrosine phosphorylation or RIP in lipid rafts (Boucher et al, 2002; von Cathepsin D, endocytosis and LRP1 RIP D Derocq et al Arnim et al, 2005;Wu and Gonias, 2005). We observed that LRP1b overproduction directs pro-cath-D to the lipid rafts (Beaujouin et al, 2010), suggesting that cath-D modulates the tyrosine phosphorylation of LRP1, as shown for the PDGF-BB (Boucher et al, 2002;Loukinova et al, 2002;Boucher and Gotthardt, 2004;Newton et al, 2005) and CTGF (Yang et al, 2004) growth factors, the tPA serine protease (Hu et al, 2006) and in fibroblasts transformed with v-Src (Barnes et al, 2001(Barnes et al, , 2003. We next investigated the effect of pro-cath-D on the tyrosine phosphorylation of LRP1b in fibroblasts.…”
Section: Resultssupporting
confidence: 68%
“…It delivers most, but not all, of these ligands to lysosomes for degradation (Herz and Strickland, 2001;Gonias et al, 2004;Emonard et al, 2005;May et al, 2007). It has also been shown that LRP1 is involved in signal transduction by phosphorylation of the tyrosine in the cytoplasmic NPXY motifs of its b-chain and modulation of signaling pathways such as the MAP kinase pathway (Barnes et al, 2001(Barnes et al, , 2003Boucher et al, 2002;Boucher and Gotthardt, 2004;Loukinova et al, 2002;Yang et al, 2004;Newton et al, 2005;Hu et al, 2006). More recent studies have shown that LRP1 influences gene transcription by regulated intramembrane proteolysis (RIP) of its b-chain (May et al, 2002;Kinoshita et al, 2003;von Arnim et al, 2005;Zurhove et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Our proposed scheme for a partial signaling pathway that enables TSPs to counteract the stimulatory effects of VEGF on cell cycle progression (Figure 10) is based in part on recent studies showing that platelet-derived growth factor (PDGF) binds and activates LRP1, an activity that results in a transient phosphorylation of tyrosine 63 in the second NPXY sequence of the LRP1 cytoplasmic domain (Boucher et al, 2002;Loukinova et al, 2002). This phosphorylation is mediated by Src or Src family members and requires the kinase domain of the PDGF ␤ receptor (Newton et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, the bridging of LRP and the PDGF receptor by a common ligand, PDGF, is apparently not necessary for the phosphorylation of LRP (Newton et al, 2005). PDGF-induced phosphorylation of LRP also produces a docking site for Shc, a group of three homologous adapter proteins that contain a carboxy-terminal Src-homology 2 (SH2), and an amino-terminal PTB domain that is involved in signal transduction by protein tyrosine kinases (Loukinova et al, 2002). Specifically, Shc has been reported to couple activated growth factor receptors to signaling pathways that regulate the proliferation of mammalian cells and plays a role in activation of MAPK (Pelicci et al,1992;Ravichandran, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation